Enhancing exercise tolerance and physical activity in COPD with combined pharmacological and non-pharmacological interventions: PHYSACTO randomised, placebo-controlled study design. Issue 4 (13th April 2016) - Troosters, Thierry; Bourbeau, Jean; Maltais, François; Leidy, Nancy; Erzen, Damijan; De Sousa, Dorothy; Korducki, Lawrence; Hamilton, Alan
Abstract : Introduction: Chronic obstructive pulmonary disease (COPD) is associated with exercise limitation and physical inactivity, which are believed to have significant long-term negative health consequences for patients. While a number of COPD treatments and exercise training programmes increase exercise capacity, there is limited evidence for their effects on physical activity levels, with no clear association between exercise capacity and physical activity in clinical trials. Physical activity depends on a number of behaviour, environmental and physiological factors. We describe the design of the PHYSACTO trial, which is investigating the effects of bronchodilators, either alone or with exercise training, in combination with a standardised behaviour-change self-management programme, on exercise capacity and physical activity in patients with COPD. It is hypothesised that bronchodilators in conjunction with a behaviour-change self-management programme will improve physical activity and that this effect will be amplified by the addition of exercise training. Methods and analysis: Patients are being recruited from 34 sites in Australia, New Zealand, the USA, Canada and Europe. Patients receiving a multicomponent intervention designed to support behaviour change related to physical activity are randomised to four treatment arms: placebo, tiotropium, tiotropium+olodaterol, and tiotropium+olodaterol+exercise training. The primary outcome is improvement in exercise capacity after 8 weeks, measured by endurance time during a shuttle walk test. The secondary outcome is improvement in physical activity, including objective accelerometer assessment and patient-reported functioning using the Functional Performance Inventory—Short Form and the novel hybrid PROactive instrument. Additionally, the influence of moderating variables (ie, factors influencing a patient's choice to be physically active) on increases in physical activity is also explored. Ethics and dissemination: The study has been approved by the relevant Institutional Review Boards, Independent Ethics Committee and Competent Authority according to national and international regulations. The findings of the trial will be disseminated through relevant peer-reviewed journals and international conference presentations. Trial registration number: NCT02085161.